VLSI circuit placement with rectilinear modules using three-layer force-directed self-organizing maps - Chang, RI; Hsiao, PY (My University, 1997)
In this paper, a three-layer force-directed self-organizing map is designed to resolve the circuit placement problem with arbitrarily shaped rectilinear modules. The proposed neural model with an additional hidden layer can easily model a rectilinear module by a set of hidden neurons to correspond the partitioned rectangles. With the collective computing from hidden neurons, these rectilinear modules can correctly interact with each other and finally converge to a good placement result. In this paper, multiple contradictory criteria are accounted simultaneously during the placement process, in which, both the wire length and the module overlap are reduced. The proposed model has been successfully exploited to solve the time consuming rectilinear module placement problem, The placement results of real rectilinear test examples have been presented, which demonstrate that the proposed method is better than the simulated annealing approach in the total wire length, Furthermore, on the average, the central processing unit (CPU) time for the proposed method running on a sequential machine is 15 times faster than that required by the simulated annealing method, The appropriate parameter values which yield good solutions are also investigated.
Keywords: force-directed placement method; molecule model; query-based learning; rectilinear circuit; three-layer self-organizing maps